2018
DOI: 10.1093/nar/gky231
|View full text |Cite
|
Sign up to set email alerts
|

DDX49 is an RNA helicase that affects translation by regulating mRNA export and the levels of pre-ribosomal RNA

Abstract: Among the proteins predicted to be a part of the DExD box RNA helicase family, the functions of DDX49 are unknown. Here, we characterize the enzymatic activities and functions of DDX49 by comparing its properties with the well-studied RNA helicase, DDX39B. We find that DDX49 exhibits a robust ATPase and RNA helicase activity, significantly higher than that of DDX39B. DDX49 is required for the efficient export of poly (A)+ RNA from nucleus in a splicing-independent manner. Furthermore, DDX49 is a resident prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 56 publications
(63 reference statements)
1
34
0
Order By: Relevance
“…Both DDX39B and DDX49 are required for efficient regulation of pre-ribosomal RNA Recently, we showed that DDX49 affects the pre-ribosomal 47S RNA levels [16] and here we find that DDX39B has a similar function. Since both DDX39B and DDX49 displayed overlapping roles in regulating pre-ribosomal RNA levels, we investigated the functional relationship between these two RNA helicases.…”
Section: Ddx39b Regulates Cell Proliferation and Is Elevated In Diversupporting
confidence: 74%
See 3 more Smart Citations
“…Both DDX39B and DDX49 are required for efficient regulation of pre-ribosomal RNA Recently, we showed that DDX49 affects the pre-ribosomal 47S RNA levels [16] and here we find that DDX39B has a similar function. Since both DDX39B and DDX49 displayed overlapping roles in regulating pre-ribosomal RNA levels, we investigated the functional relationship between these two RNA helicases.…”
Section: Ddx39b Regulates Cell Proliferation and Is Elevated In Diversupporting
confidence: 74%
“…Our findings presented here on the regulation of pre-ribosomal levels, adds DDX39B to this list. Recently, we reported that DDX49 regulates the steady state levels of pre-ribosomal 47S RNA [16]. Here, we show that both DDX49 and DDX39B are essential for efficient regulation of 47S rRNA in the cell.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…We found that down-regulation of DDX49 in NSCLC cells significantly suppressed NSCLC cell growth and migration. Sharad Awasthi also proposed a similar conclusion: DDX49 displays a robust ATPase and RNA helicase activity and it is involved in the export of poly (A) + mRNAs to cytoplasm, DDX49 affects cell proliferation and its aberrant expression might have oncogenic potential 6 . We found that these genes were more likely involved in the PI3K/Akt pathway, cell and metabolic pathways, and focal adhesion by KEGG pathway analysis.…”
Section: Discussionmentioning
confidence: 84%